Impact of Educational Programs on the Knowledge and Attitude of Healthcare Professionals in Antimicrobial Stewardship - Lutfiyati, Heni; At Thobari, Jarir; Yasin, Nanang Munif; Ikawati, Zullies (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: The main concern related to antimicrobial use is the increasing incidence of resistance. Objective: This study aims to assess the impact of educational programs on the knowledge, attitudes, and practices of healthcare providers concerning antimicrobial Stewardship (AMS) in hospitals. Materials and Methods: This is a quasi-experimental study with one group pretest-posttest design. Health professionals were requested to complete an online questionnaire before and after educational programs. This is a 2-day workshop conducted through the virtual zoom platform. Results: Regarding the basic prior knowledge, all respondents completely agree that inappropriate use of antibiotics can lead to resistance, can lead to ineffective treatment and burdens patients with additional medical costs and majority agree that inappropriate use of antibiotics can worsen side effects (91.7%). Regarding familiarity of health professionals, very familiar/familiar with the term of antimicrobial stewardship (75.0%), term of antibiotic resistance (86.1%), term of DDD/DOT (52.8%), while the majority of health professionals were not familiar/ not all familiar with the term of antibiogram (66.7%) and Gyssens (55.6%). About the effectiveness of antimicrobial stewardship, all respondents 100% answered that antimicrobial stewardship was effective in reducing resistance and health care costs, improving patient safety (97.2%) and only 11.11% answered not effective to improve outcomes. The level of knowledge of health professionals did not change significantly, but the perception increased significantly after the educational intervention, p-value<0.005. Conclusion: The educational program implemented is effective in improving the attitudes of health professionals about antimicrobial stewardship.
Keywords: Education; Antimicrobial stewardship; Knowledge; Attitude; Healthcare professional